A new Friesea of the mirabilis-group from Algeria (Collembola: Neanuridae: Frieseinae) - Kroua, Salah Hamra; Jordana, Rafael; Deharveng, Louis (Zootaxa, 2009)
As noted in a previous paper (Deharveng & Hamra-Kroua 2004), Friesea are well diversified in Eastern Algeria. This fauna includes species from two different taxonomic groups. First, a complex of forms closely related to Friesea afurcata Denis, 1926 includes Friesea ladeiroi Gama, 1959 and Friesea laouina Deharveng & Hamra-Kroua, 2004 in the studied region. They exhibit various degrees of intra-population eye reduction (from 8+8 to absence of eyes) of unknown taxonomic meaning that are currently under scrutiny (Jordana & Deharveng, unpublished observations). Second, the mirabilis group sensu Deharveng & Bedos (1991), distributed worldwide, includes a large number of described and undescribed forms of disputable status, due to the high level of polymorphism which affects most of the taxonomic characters: chaetal arrangement, tenent hair capitation, chaeta morphology, mucro (when reduced), eye number (when reduced). We described here a new species of this group from Algeria. Abbreviations. Abd––abdominal segment, Ant––antennal segment, Th––thoracic segment, Tita––tibiotarsus. Material deposit. LBEA––Laboratoire de Biosystématique et Ecologie des Arthropodes, Faculté des Sciences de la Nature et de la Vie, Université Mentouri, Constantine (Algérie); MNHN––Muséum National d’Histoire Naturelle de Paris (France); MZNA––Museo de Zoología, University of Navarra, Pamplona (Spain).